2021
DOI: 10.3892/ol.2021.12632
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA LINC00173 enhances cisplatin resistance in hepatocellular carcinoma via the microRNA‑641/RAB14 axis

Abstract: A growing body of evidence indicates that long non-coding RNAs (lncRNAs) play crucial roles in the chemoresistance of human cancers. However, the molecular mechanisms underlying the functions of certain lncRNAs in the chemotherapeutic resistance of hepatocellular carcinoma (HCC) remain unclear. The aim of the present study was to investigate the function and potential mechanism of action of lncRNA LINC00173 in HCC cisplatin (DDP) resistance. Reverse transcription-quantitative PCR analysis indicated that LINC00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…We found that LINC00173 expression is deregulated in all tumors, being underexpressed in 13 different tumor types (Log2FC > 1, p < 0.01, Supplementary Figure 10 ). Some of them have been reported previously ( 22 , 23 , 26 , 29 31 ), but underexpression and overexpression of LINC00173 were observed in six (DLBC, KICH, OV, THCA, UCEC, and UCS) and one (KIRC) non-reported tumor type, respectively ( Figure 6A ). After exploring the role of LINC00173 expression status in DFS and OS in the unreported tumors, we found that this lincRNA is related to the risk of relapse and death in all these cancer types (log2HR > 1, p < 0.05, Figures 6B , C ).…”
Section: Resultssupporting
confidence: 56%
“…We found that LINC00173 expression is deregulated in all tumors, being underexpressed in 13 different tumor types (Log2FC > 1, p < 0.01, Supplementary Figure 10 ). Some of them have been reported previously ( 22 , 23 , 26 , 29 31 ), but underexpression and overexpression of LINC00173 were observed in six (DLBC, KICH, OV, THCA, UCEC, and UCS) and one (KIRC) non-reported tumor type, respectively ( Figure 6A ). After exploring the role of LINC00173 expression status in DFS and OS in the unreported tumors, we found that this lincRNA is related to the risk of relapse and death in all these cancer types (log2HR > 1, p < 0.05, Figures 6B , C ).…”
Section: Resultssupporting
confidence: 56%
“…Extensive studies have shown that lncRNAs served as vital functions in the drug resistance of HCC [ 5 , 6 ]. For instance, LINC01234 accelerated HCC cell line progression and chemoresistance by targeting the miR-31-5p/MAGEA3 axis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of AC015813.1 in KIRC remains unknown. As for LINC00173, its high expression promoted the progression of cervical cancer by targeting miR-3171 [ 50 ], hepatocellular carcinoma via the microRNA-641/RAB14 axis [ 51 ], triple-negative breast cancer [ 52 ], glioma through sponging miR-765 [ 53 ], colorectal cancer by regulating the miR-765/PLP2 axis [ 54 ], and lung squamous cell carcinoma by sponging miR-511-5p to regulate VEGFA expression [ 55 ]. In other studies, LINC00173 was reported to inhibit pancreatic cancer by repressing sphingosine kinase 1 protein expression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%